Deus sob as coisas: o pensamento espiritual de Chiara Lubich sobre a natureza - Testa, Fernando Gregianin (2010)
This study focuses on Chiara Lubich's thought on physical nature using phylosophical and theological key points. Italian, catholic and foundress of the Focolare Movement, Chiara s reflection is on nature starting from a Christian lifeworld in order to progressively interpret all of human and natural reality. After going through the historical roots and the basics of Chiara Lubich s spirituality, some mystical writings are presented, especially those concerning the Creation and nature. The theological depth of spirituality is, then, discussed by means of the aspects of Unity and Jesus Forsaken. The first can be understood as the unity of the Trinity, fruit of perichoresis but also as the presence of Christ in the community. The second, a particular understanding of the Cross of Christ. The relationship between these two aspects and their understanding that occur in the community through the action of the Spirit indicate that the very approach to the mystery of the paschal event is trinitarian. This is the theological source from where Lubich understands nature. The similarities between Chiara Lubich s thought and the franciscan tradition are presented. Her understanding of the Creation is expressed, then, in boaventurian style. This conception of the Trinity is experienced in a mystical form and forges a representation of the actual structure of the world. Her specific religious thought on nature is that the objects, relationships, natural events and the whole cosmos are conceived in a dynamism of the Trinity and have, thus, a Trinitarian ontology. This conception about nature is oriented to detect those connections of meaning: the trinitarian ontology as a heuristic method that evolves from the Trinitarian mystery to understand nature. Still, the religious thought of Lubich has characteristics of critical realism: scientific and religious knowledge express the Trinitarian structure of reality through their respective methods and awareness of their provisional status. Religion is also studied in its natural appearance by means of the cognitive sciences, which are interpreted within the same critical realist framework of the trinitarian ontology. Finally, a parallel is drawn between epistemic procedures of religion, as it can be seen in Lubich, and natural science reinforcing both the idea of the autonomy of religious thought and its positive epistemic status